Gender, ownership and engagement during the European Union referendum: gendered frames and the reproduction of binaries. Issue 3 (29th November 2018) - Guerrina, Roberta; Exadaktylos, Theofanis; Guerra, Simona
Abstract : The European Union referendum was supposed to be a significant moment for political engagement and ownership in the UK. This article looks at how the two official European Union referendum campaigns (Vote Leave and Remain) framed discussions about the UK's membership of the European Union, as well as the impact of the campaign on women's political activation. Using data from a survey questionnaire conducted two weeks after the European Union referendum (in July 2016), we analyse women's sense of political efficacy and engagement with European politics. We project those findings on a frame analysis, where we assess the footprint of each campaign in terms of issue coverage and the salience of gender as a campaign issue. Our findings shed light on the way in which issue framing and confidence affect the quality of political engagement among 'weak publics'.